2007
DOI: 10.1038/sj.onc.1210881
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage signalling guards against activated oncogenes and tumour progression

Abstract: DNA damage response (DDR), the guardian of genomic integrity, emerges as an oncogene-inducible biological barrier against progression of cancer beyond its early stages. Recent evidence from both cell culture and animal models as well as analyses of clinical specimens show that activation of numerous oncogenes and loss of some tumour suppressors result in DNA replication stress and DNA damage that alarm the cellular DDR machinery, a multifaceted response orchestrated by the ATR-Chk1 and ATM-Chk2 kinase signalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
413
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 474 publications
(424 citation statements)
references
References 33 publications
8
413
0
3
Order By: Relevance
“…A senescence-like phenotype of doxorubicin-treated fibroblasts in G2 To investigate the cellular response to genotoxic stress at the level of APC/C regulation we used primary fibroblasts, as most transformed cell lines have acquired genetic alterations in DNA damage checkpoint pathways (Bartek et al, 2007). In particular, we wanted to address whether the silent APC/C of S/ G2 cells could be activated in response to DNA damage.…”
Section: Resultsmentioning
confidence: 99%
“…A senescence-like phenotype of doxorubicin-treated fibroblasts in G2 To investigate the cellular response to genotoxic stress at the level of APC/C regulation we used primary fibroblasts, as most transformed cell lines have acquired genetic alterations in DNA damage checkpoint pathways (Bartek et al, 2007). In particular, we wanted to address whether the silent APC/C of S/ G2 cells could be activated in response to DNA damage.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from aging, several different stimuli can trigger senescence in normal human cells. For instance, oncogene activation in normal cells induces a permanent proliferative arrest termed oncogene-induced senescence, which functions as a barrier to cell transformation (Braig and Schmitt, 2006;Bartek et al, 2007). Although cancer cells bypass both replicative and oncogene-induced senescence, the genetic program of senescence in these cells seems to be repressed, but not lost, in such a way that it can be reactivated by expression of critical regulators.…”
Section: Introductionmentioning
confidence: 99%
“…It is proposed that the DDR machinery acts as an anticancer barrier, protecting cells against the progression of tumors from their early stages into malignant invasive lesions. 19 In a seminal paper, Bartkova et al 4 demonstrated that several human tumors (but not normal tissue) express markers of an activated DDR, including ATM, Chk2, phosphorylated H2AX, and p53, in their very early premalignant stages. Tort et al 30 recently showed in human colon adenomas that high-risk grade III adenomas show multiple markers of DDR activation, whereas low-grade adenomas (grades I and II) lack detectable markers of activated DDR.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, we observed the constitutive activation of DNA damage checkpoints exclusively in FTC with a combined overexpression of S-phase promoting cell-cycle kinases cyclin E, E2F1, and Rb1. Because it is hypothesized that among the early lesions of the same tissue the DDR barrier becomes only alarmed in those tumors that bear a higher risk of malignant progression, 4,19 these data could suggest that FAs evolve distinctly from FTCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation